The Effect of Endurance Training and L-Carnitine Consumption on TNF-a and IL-1β Gene Expression of Heart Tissue in Wistar Male Rats following Anabolic Steroid Consumption (Boldenone) - pooran adyani; Asieh Abbassi-Daloii; saeedeh shadmehri (Fasa University of Medical Sciences, 2019)
Background & Objective: The aim of this study was to investigate the effect of endurance training and L-carnitine consumption on TNF-a and IL-1β gene expression of heart tissue in Wistar male rats following anabolic steroid consumption (Boldenone). Materials & Methods: In this experimental study, 30 male Wistar rats aged 12 weeks (weight 195±7.94g) were randomly divided into five groups including control, no-treatment, boldenone (5mg/kg), L-carnitine and aerobic training- L-carnitine. The endurance moderate intensity training program (55-50% of maximal oxygen consumption) was performed for 6 weeks and 5 times a week. Injection was conducted once a week, on an appointed day, and in the quadriceps and hamstring it was conducted in depth. After anesthesia, autopsy was performed and the heart was isolated. The TNF-α and IL-1β gene expression in the samples was measured by Real Time PCR. Data were analyzed using t-test, One-way ANOVA and post hoc Scheffe at the significant level of P<0.05. Results: The results showed that there was a significant difference between the mean TNF-α and IL-1β gene expression of heart tissue in male Wistar rats in different groups (P=0.001). The changes in TNF-α and IL-1β gene expression of heart tissue in L-carnitine and Training-L-carnitine groups were significantly lower than those of the no-treatment and boldenon groups (P=0.001). Conclusion: It seems that supplementation of L-carnitine with regular aerobic training reduces heart tissue damage induced by anabolic androgenic steroids.